2014
DOI: 10.1039/c4cc07093c
|View full text |Cite
|
Sign up to set email alerts
|

Potential-dependent hydration structures at aqueous solution/graphite interfaces by electrochemical frequency modulation atomic force microscopy

Abstract: Potential-dependent solvation structures of aqueous electrolyte-graphite interfaces were studied using electrochemical frequency modulation atomic force microscopy. Oscillatory modulations on the force curves reversibly changed with the applied potential on the graphite electrode, and also strongly depended on the anion species in electrolyte solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…The structural solvation forces observed at liquid/solid interfaces have been an important subject for elucidating molecular-scale interface structures. 38,[47][48][49][50][51][52][53][54][55][56] Previous studies of IL/solid interfaces have revealed that the structural solvation layer spacing of ILs agrees well with the ionpair diameter calculated from the cubic root of the volume per IL ion pair (molecular volume). 52 The spacings of the valleys Thick and thin lines represent the approach and retraction curves, respectively.…”
Section: High Resolution Imagingmentioning
confidence: 85%
See 1 more Smart Citation
“…The structural solvation forces observed at liquid/solid interfaces have been an important subject for elucidating molecular-scale interface structures. 38,[47][48][49][50][51][52][53][54][55][56] Previous studies of IL/solid interfaces have revealed that the structural solvation layer spacing of ILs agrees well with the ionpair diameter calculated from the cubic root of the volume per IL ion pair (molecular volume). 52 The spacings of the valleys Thick and thin lines represent the approach and retraction curves, respectively.…”
Section: High Resolution Imagingmentioning
confidence: 85%
“…The experimental details are described elsewhere. [33][34][35][36][37][38] Gold backcoated cantilevers (Tap 300GD-G, BudgetSensors or PPP-NCHAuD, Nonosensors) with approximately 40 N m À1 force constants were used. The cantilever surfaces were cleaned prior to use by the method proposed by Fujihira et al 39 All FM-AFM images presented in this study are topographies obtained at a constant frequency shift (Df ) and at a constant vibrational amplitude (A p-p ).…”
Section: Methodsmentioning
confidence: 99%
“…With improvements of experimental techniques it has become possible to image solid-water interfaces with unprecedented detail [4]. A common observation at these interfaces is the layered arrangement of water: Hydration layers have been observed at a large variety of solid-water interfaces, including mineral-water interfaces [5][6][7], graphite-water [8], and metalwater interfaces [9,10]. Layers at solid-water interfaces have been observed using x-ray reflectivity measurements [11][12][13], the surface force apparatus [14][15][16][17], and with high-resolution three-dimensional (3D) atomic force microscopy (AFM) [5].…”
mentioning
confidence: 99%
“…[ 9d ] Simulation on the dynamics of the hydration layers shows that the negative potential is more disruptive. [ 9e ] Experimentally, the formation and the structure of hydration layer was measured by scanning probe microscopy [ 10 ] and X‐ray reflectivity. [ 11 ] An interesting experimental evidence of the hydrophobic hydration layer is the reversible wettability of graphene on UV exposure that forms oxygen and hydroxyl radicals that react with graphene to make the interface hydrophilic which can be reversed to hydrophobic surface on storing in the dark.…”
Section: Introductionmentioning
confidence: 99%